Revisiting the Poverty Trend in Rwanda : 2010/11 to 2013/14 - Fatima, Freeha (World Bank, Washington, DC, 2018)
According to the official statistics published by the National Institute of Statistics of Rwanda, the country registered a decline in poverty from 46 percent in 2010/11 to 39 percent in 2013/14. This declining poverty trend was broadly debated and repeatedly questioned in national and international forums, which provided the primary motivation for this study. Using data from the third and fourth rounds of the Integrated Household Living Conditions Surveys, this paper revisits the national poverty numbers and corroborates the poverty rates published by the National Institute of Statistics of Rwanda. Underlying the paper’s conclusions is a detailed theoretical and analytical framework for making poverty comparisons over time. Furthermore, the paper shows that after adjusting for spatial and temporal price differences, the poverty rate based on the international poverty line of $1.90 per day per capita shows that there was a reduction in poverty between 2010/11 and 2013/14.